INDUSTRY AND ACADEMIC EXPERTS MEET TO DISCUSS ON 'WHAT'S CHOKING THE ROAD TO SUCCESS?' - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
BUKIT JAMBUL, 26 May 2016 For every company, which has successfully entered the market, there are many more which continue to seek access to the latest technologies, innovative research and a wealth of knowledge in order to catalyse financial growth and business expansion.